2011
DOI: 10.1074/jbc.m111.254995
|View full text |Cite
|
Sign up to set email alerts
|

Human Mutation within Per-Arnt-Sim (PAS) Domain-containing Protein Kinase (PASK) Causes Basal Insulin Hypersecretion

Abstract: Background: The glucose sensor PAS kinase (PASK) plays a fundamental role in pancreatic islet physiology.Results: A single amino acid substitution in the human PASK kinase domain stimulates enzyme activity and increases insulin secretion at low glucose.Conclusion: A rare, naturally occurring mutation in PASK modulates insulin release in man.Significance: We provide direct genetic evidence for a role for PASK in controlling insulin secretion in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…By performing a cycloheximide chase experiment, here we found that PDX-1 protein stability was enhanced in MIN6 cells overexpressing WT hPASK but not the KD form in both MIN6 cells and isolated rat islets. Consistent with previous data (24,26), overexpression of WT hPASK did not affect PDX-1 mRNA expression (data not shown), consistent with a mainly posttranslational effect. Importantly, overexpression of KD GSK3␤ blocked PDX-1 degradation in cells overexpressing KD PASK, thus demonstrating the requirement for GSK3␤ in PASK regulation of PDX-1 stability.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…By performing a cycloheximide chase experiment, here we found that PDX-1 protein stability was enhanced in MIN6 cells overexpressing WT hPASK but not the KD form in both MIN6 cells and isolated rat islets. Consistent with previous data (24,26), overexpression of WT hPASK did not affect PDX-1 mRNA expression (data not shown), consistent with a mainly posttranslational effect. Importantly, overexpression of KD GSK3␤ blocked PDX-1 degradation in cells overexpressing KD PASK, thus demonstrating the requirement for GSK3␤ in PASK regulation of PDX-1 stability.…”
Section: Discussionsupporting
confidence: 81%
“…Importantly, however, PASK mRNA levels are reduced and are no longer responsive to glucose in islets from type 2 diabetic humans (35). Recently, we have identified two rare mutations in the pask gene associated with early onset diabetes (26). One of these induced an ϳ2-fold increase in PASK activity, and its expression in islets increased basal insulin secretion and gene expression, supporting an important role for PASK in human ␤-cell function.…”
Section: Discussionmentioning
confidence: 98%
“…The deregulation of these signalling pathways might be involved in the development of obesity and type 2 diabetes. A mutation in the PASK gene has been described in the early onset of diabetes, which modulates glucose-stimulated insulin secretion [43]. A decrease in PASK expression was also found in pancreatic islets from human with type 2 diabetes [8].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the mutated PASK (G1117E) has ~25 % higher activity than wild-type PASK and overexpression of this kinase variant led to a left-shift in the glucose response in mouse pancreatic islets. As a result, glucose-stimulated insulin secretion and insulin gene expression were increased at normally non-permissive (3 mM) glucose concentrations (72).…”
Section: Pas Domain Containing Protein Kinase (Pask)mentioning
confidence: 99%
“…Importantly, PASK expression is lower in the cells of patients with type 2 diabetes in comparison to cells of non-diabetic individuals (49). Very recently, an activating mutation in PASK was identified which is associated with non-autoimmune early-onset diabetes in humans (72). However, this mutant did not fully co-segregate with the disease and appears to serve as a modifier for a separate disease-causing mutation in another gene.…”
Section: Pas Domain Containing Protein Kinase (Pask)mentioning
confidence: 99%